Prevalencia de parásitos gastrointestinales en cuyes (cavia porcellus) en el barrio San Jacinto del canton Ambato de la provincia de Tungurahua - Coello Zamora, Darío Leodán (2021)
This research seeks to establish the prevalence of gastrointestinal parasitosis in guinea pigs (Cavia porcellus) of producers in the San Jacinto neighborhood in the canton of Ambato, province of Tungurahua, in order to achieve an effective sanitary management of family farms, seeking in this way to increase the productive yields of the same, for which a quantitative coprological study was carried out using the technique of flotation in sucrose itself that allowed us l to identification of intestinal parasites of the genus helminths. To carry out this study, 100 random samples were collected, taking as variables the sex and the stage of production in which the individuals were. The number of positive cases was 81% having a prevalence of parasites according to sex and growth stage in breeding females 28% and replacement was obtained 28% and for males was 5% positive cases for breeders and 20% for male fattening or destined for the carcass. The parasite with the highest prevalence was Paraspidodera uncinata with a prevalence of 41%; followed by Ascaris sunn with 24%; then Thrichuris with 21% and finally Coccidias with 13% of the total parasitic load found. However, it should be noted that Ascarsi sunn is a parasite typical of pigs. Finally, the results reveal the existence of a great parasitic difference according to sex, which is why it is recommended to carry out a periodic deworming protocol to improve the production and reproduction of their animals to obtain better economic returns for the better sustenance of the families dedicated to this activity.